பழநிபாரதியின் படைப்புகளில் பெண்கள் மீதான மனிதம் / Humanity on Women in the Works of Palanibharati - முனைவர் சா. ஜெகன்அண்டோதிலக் / Dr. S. Jeganandothilak (Pandian Journal of Women's Studies)
In the course of social dialectics, the contribution of literature is very important in helping to understand social life. Literature shows itself the society and its originality explained as a product of social importance. Therefore, literature is the basis for understanding any society and the life of the people. The writer chooses the theme for his creation from the lives of the people. The writer who takes the life of the people as the subject not only registers the social life of the people but also expresses his desire. It can be seen through his creation. At the same time, One can see that the writer presents a critique of society in his work. It can be observed that there is an ideal society desired by the creator is displayed in his presentation. The writer explains how he presents his ideologies of social trends through his work. Thus, the ideological background he presents reveals the thinking and philosophical background of the writer. Therefore, to understand the social observation of the writer, it is necessary to understand the philosophical background which he discusses in his work. So, this article examines the concept of humanity on women as seen in the select works of Palanibharati.